2013
DOI: 10.1093/hmg/ddt161
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study in a Chinese population with diabetic retinopathy

Abstract: Diabetic retinopathy (DR) is a leading cause of preventable blindness in adults. To identify genetic contributions in DR, we studied 2071 type 2 diabetics. We first conducted a genome-wide association study of 1007 individuals, comparing 570 subjects with ≥8 years duration without DR (controls) with 437 PDR (cases) in the Chinese discovery cohort. Cases and controls were similar for HbA1c, diabetes duration and body mass index. Association analysis with imputed data identified three novel loci: TBC1D4-COMMD6-U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 50 publications
1
76
0
Order By: Relevance
“…Of note, four of the previously published studies were conducted in non-European populations (Chinese [17], Taiwanese [18], Japanese [19] and Mexican American [15]), while one was predominantly in patients with type 1 diabetes mellitus [16]. These fundamental differences may explain the lack of replication observed not only with the current study, but also with each other.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Of note, four of the previously published studies were conducted in non-European populations (Chinese [17], Taiwanese [18], Japanese [19] and Mexican American [15]), while one was predominantly in patients with type 1 diabetes mellitus [16]. These fundamental differences may explain the lack of replication observed not only with the current study, but also with each other.…”
Section: Discussionmentioning
confidence: 60%
“…We first assessed loci reported in previous GWAS of diabetic retinopathy [15][16][17][18][19] for association in the current study in an attempt to replicate previous findings. A p value of <0.002 was required to account for the 29 loci assessed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several genome-wide association studies (GWAS) in Mexican-Americans [21], Chinese [22], [23] and Caucasians [24] identified multiple susceptibility loci to DR; however, none of these loci reached the genome-wide significance level, and none has been replicated in other studies [14].…”
Section: Introductionmentioning
confidence: 99%